2022
DOI: 10.5455/njcm.20210602064325
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Pattern of Bacterial Isolates from Urine Samples from Female Patients Suffering From Urinary Tract Infection at Tertiary Care Center in South India

Abstract: Introduction:  The frequency of bacteria affecting urinary tract and their antibiotic susceptibility pattern vary from one territory to another. This study was conducted to determine spectrum of bacterial isolates causing UTI and their antibiotic susceptibility pattern among female patients attending tertiary care center Materials and Methods: A total of 577 female urine culture sensitivity reports (CS) were collected. The culture was done by inoculation by standard loop technique. Antibiotic susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…2021), which found a growth rate of 33.96%. 4,21,27 Our research also found that females exhibited a higher growth rate (59.40%) compared to males (40.60%). These findings align with previous studies conducted by Pritam 2022), where females showed growth rates of 66.78%, 66.8%, 62.90%, and 60%, respectively, while males exhibited growth rates of 33.22%, 33.2%, 37.10%, and 40%.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…2021), which found a growth rate of 33.96%. 4,21,27 Our research also found that females exhibited a higher growth rate (59.40%) compared to males (40.60%). These findings align with previous studies conducted by Pritam 2022), where females showed growth rates of 66.78%, 66.8%, 62.90%, and 60%, respectively, while males exhibited growth rates of 33.22%, 33.2%, 37.10%, and 40%.…”
Section: Resultssupporting
confidence: 69%
“…21 Some of the powerful drugs like penicillin, third generation cephalosporins ceftazidime, and cefotaxime, fluoroquinolones like ciprofloxacin, aminoglycosides like amikacin and gentamicin have revolutionized the treatment. 21 Treatment with antibiotics is the empirical therapy used for the UTIs but in some cases empirical therapy is started even before the culture and sensitivity report that also with latest antibiotics. 21 Urinary tract infections (UTIs) are typically treated with antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing our study’s findings to those of other studies conducted outside of the study area and Africa, it is clear that antimicrobial resistance in Escherichia coli infections is a global concern. a study conducted in India found high rates of resistance to commonly used antibiotics such as norfloxacin and ciprofloxacin ( Vidya et al, 2021 ). Similarly, a study conducted in Zimbabwe found high rates of resistance to ciprofloxacin and Cefotaxime ( Demilie et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%